Seroprevalence of Neospora caninum in dairy cattle from north-west and centre of Romania - Gavrea, R.R. (EDP Sciences, 2011)
Neosporosis is a disease that mainly affects cattle in both dairy and beef herds. The main definitive host of this parasite is the dog. Since 1984 and its first description a large number of data were published worldwide on this parasite. In Romania, the research regarding this parasite is limited. The purpose of this study was to determine the seroprevalence of Neospora caninum infection in dairy cattle from six regions in north-western Romania and to evaluate the intensity of infection in different animals groups. A total number of 901 samples (862 sera from adult cows and 39 sera from calves) were collected from dairy farms and were screened for the presence of specific IgG anti-bodies using an enzyme-linked immunosorbent assay (ELISA). The overall seroprevalence for neosporosis was 34.6%. In adult cows and calves seroprevalences reached 34.8% (300/862) and 30.8% for calves (12/39) respectively. In cattle which had previously aborted, seroprevalence was 40.9%. These results indicate that N. caninum infection is widespread among animals reared in dairy systems from Romania and a program for farmer training and a strategy for reducing the economic impact of the disease are needed.